Knowledge, Attitudes, Income and Implementation Regarding the Dengue Fever Prevention Program in Medan, Indonesia - Heppy Santhi; Irnawati Marsaulina; Nurmaini (Britain International of Exact Sciences (BIoEx) Journal, 2020)
The best program to control the spread of dengue infection is a dengue prevention program. Indonesia has a dengue prevention program known as 3M Plus. Medan City is one of the endemic areas of dengue fever in Indonesia. This study aims to evaluate the knowledge, attitude and income implementation of the dengue prevention program in Medan. Information on sociodemography, knowledge, attitudes, and implementation of dengue prevention was collected using a semi-structured questionnaire that had been tested previously. This cross-sectional survey was conducted with face-to-face interviews with 100 randomly selected heads of households. Bivariate analysis using chi-square test. The results showed that overall participants had low family income, poor dengue knowledge, moderate attitude and moderate prevention implementation. There was a significant positive relationship between family income and implementation of dengue prevention (p = 0.001), knowledge and implementation of dengue prevention (p = 0.012), and attitudes and implementation of dengue prevention (p <0.001). In conclusion, dengue prevention programs require increased knowledge, attitudes and implementation of dengue prevention. Households with an income below the city minimum wage must be the main target of the dengue prevention campaign. Knowledge-based campaigns and arousing positive attitudes will increase the application of dengue prevention.